Media Relations Strategy in Building Positive Image of the Institution - Abduh, Muhammad (Communicatus: Jurnal Ilmu komunikasi, 2022)
Media relations is one of the determining strategies in building the institution's image. The research aims to determine the Media Relations Strategy by Public Relations of Bank Indonesia West Java Province in building a positive image of the institution. The qualitative method used in this research uses descriptive analysis to describe a situation or event. It gives a detailed description of specific individuals or groups regarding the circumstances and symptoms. Theoretically or conceptually, this research is based on Rosady Ruslan's concept of media relations which is divided into three, namely Media Gathering, Media Tour, and Press Conference. The data collection in this study is by interviews and observations with four informants. The results of this study indicate that the Media Relations Strategy carried out by Bank Indonesia Public Relations in West Java Province includes three activities: Media Gathering, Media Tour, and Press Conference activities. This research is hoped to impact the development of public relations science and public relations practices in companies. Â